Geopolymer composition and manufacturing method therefor

By using a geopolymer composition with sodium metasilicate powder and reduced water content, the challenges of achieving high strength in water without additives are addressed, enabling the application of high-strength geopolymer concrete in underwater environments.

JP2025060445APending Publication Date: 2025-04-10IHI CORP +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024163933
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-09-20
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Conventional geopolymer compositions struggle to achieve sufficient strength when solidified in water due to their different solidification processes and properties compared to cement, and they require specific warming and curing steps which are not feasible in underwater environments.

Method used

A geopolymer composition made from a mixture of an active filler, an alkaline raw material (sodium metasilicate powder), and water, which is filled into water to solidify, reducing the water content and allowing for high-density geopolymer production without the need for additives like organic thickeners or surfactants.

Benefits of technology

The geopolymer composition achieves high strength similar to that in air, even when solidified in water, without the need for heating or curing, and can be applied to underwater structures utilizing its high chemical resistance and elemental confinement properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060445000001_ABST
    Figure 2025060445000001_ABST
Patent Text Reader

Abstract

To provide a geopolymer composition which has high viscosity and non-separation property of materials in water without using additives such as organic thickeners or surfactants as in conventional cement-based materials, and which can exhibit high strength comparable to that in the air even in water where heating curing cannot be performed; and also to provide a manufacturing method therefor.SOLUTION: As sodium metasilicate powder is used as an alkali raw material of a geopolymer composition that is filled and solidified in water, the water content in the raw materials can be significantly reduced as compared to the case where water glass is mainly used as the alkali raw material, the geopolymer can be densified, and the filling strength in water can be increased. Accordingly, even without using additives such as organic thickeners or surfactants as in conventional cement-based materials, the composition can exhibit high viscosity and high material non-separation property in water, and can also exhibit high strength in water where heating curing cannot be performed, comparable to that in the air.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a geopolymer composition for underwater application of geopolymer concrete used in structures in civil engineering, architecture, etc., and a method for producing the same. [Background technology]

[0002] Traditionally, structures in civil engineering, architecture, and the like have generally been made from concrete and mortar. In recent years, however, geopolymer compositions have been attracting attention as alternative materials to concrete and mortar, and their application to various concrete structures as geopolymer concrete has been considered (see, for example, Patent Document 1).

[0003] A geopolymer composition is a hardened body obtained by mixing and reacting an alkali-active amorphous powder (active filler) such as fly ash (coal ash), metakaolin, or blast furnace slag with an alkaline solution that activates it. Geopolymer concrete is a composition that exhibits strength equivalent to that of cement concrete, for example, by adding fine aggregate, coarse aggregate, etc. to an alkali-active amorphous powder and an alkaline solution.

[0004] Traditionally, geopolymer concrete has been used in research and test construction for precast products that include a heat curing process, and in on-site construction for repair purposes. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 5091519 Summary of the Invention [Problem to be solved by the invention]

[0006] Incidentally, when cement concrete materials are used for underwater construction of marine structures, etc., the cement concrete materials are easily mixed with water and separation of the materials occurs in the water. Therefore, in order to carry out underwater construction, it is necessary to add anti-separation admixtures such as organic thickeners and surfactants, and water reducers to improve workability.

[0007] In addition, unlike conventionally used cement, geopolymers are materials that solidify through dehydration condensation polymerization. Therefore, in an environment where there is an excess of water in terms of chemical equilibrium and reaction kinetics, the solidification rate slows down. In addition, geopolymer paste before solidification is easy to mix with water, just like cement. However, since the solidification process and properties of geopolymers are different from those of cement, admixtures and water reducers for cement cannot be used. Furthermore, geopolymers require an appropriate heating and curing process to develop sufficient strength. Due to these properties, conventional geopolymers could not obtain sufficient strength when solidified underwater.

[0008] However, due to the high chemical resistance of geopolymers, there is a high demand for their application to marine structures, etc., and it is hoped that they will be applied underwater in the ocean, rivers, etc. in the future. In addition, because geopolymers have the characteristics of high element containment and high heat resistance, there is also demand for their application in the nuclear field. Nuclear reactors always require cooling with cooling water to remove decay heat from the fuel. Also, taking into consideration the radiation shielding effect of water and the prevention of dust scattering, construction in an underwater environment is necessary to safely proceed with decommissioning work.

[0009] The present invention has been made in consideration of the above problems, and its purpose is to provide a geopolymer composition that has high viscosity and material non-separation in water without using additives such as organic thickeners and surfactants as in conventional cement-based materials, and can exhibit high strength similar to that in air even in water where warm curing cannot be performed, and a method for producing the same. [Means for solving the problem]

[0010] In order to achieve the above object, the present invention provides a geopolymer composition which is made by mixing a material containing an active filler, an alkali source, and water, and is filled in water and solidified. The alkali source is sodium metasilicate powder.

[0011] Thus, by using sodium metasilicate powder as the alkaline raw material, it is possible to significantly reduce the moisture content of the raw material compared to the case where water glass is mainly used.

[0012] In order to achieve the above object, the present invention provides a method for producing a geopolymer composition which is made by mixing a material containing an active filler, an alkaline raw material, and water, and which is filled into water and solidified. The method uses sodium metasilicate powder as the alkaline raw material, and uses a first material transport path for transporting at least a first material containing an active filler, and a second material transport path for transporting a second material containing at least water or an alkaline solution. The first material is transported from the first material transport path, and the second material is transported from the second material transport path. The second material is added to the first material transported from the first material transport path to generate a geopolymer composition and fill it into the water.

[0013] As a result, by using sodium metasilicate powder as an alkaline raw material, it is possible to significantly reduce the raw material moisture content compared to when water glass is mainly used. In addition, a first material containing at least an active filler is transported by a first material transport path, and a second material containing at least water or an alkaline solution is transported by a second material transport path, and a geopolymer composition is generated by adding a second material transported from a second material transport path to a first material transported from a first material transport path, so that a powder material (first material) and a liquid material (second material) are transported separately, and compared to the case where the materials of the geopolymer composition are mixed and transported from the beginning, a high pressure load due to viscosity is not generated. Effect of the Invention

[0014] According to the present invention, the water content of the raw material can be significantly reduced compared to when water glass is mainly used, so that the geopolymer can be made dense and the underwater filling strength can be increased. As a result, even without using additives such as organic thickeners and surfactants as in conventional cement-based materials, the viscosity and material non-separation in water are high, and high strength similar to that in air can be expressed even in water where warm curing cannot be performed, so that it is possible to apply it to underwater structures that take advantage of the characteristics of geopolymers, such as high chemical resistance and element containment. In addition, according to the present invention, since the powder material and the liquid material can be separated and transported, it is possible to realize on-site construction of geopolymer concrete by long-distance pressure transport without generating high pressure transport load due to viscosity compared to the case where the material of the geopolymer composition is mixed and transported from the beginning. This is extremely advantageous for sites where the material transport distance to the construction site is long, such as underwater construction in the ocean or river. In addition, in order to safely proceed with construction in an underwater environment in decommissioning work at a nuclear power plant, it is effective to discharge the material to the construction site by remote control, but the present invention, which enables long-distance pressure transport even in such cases, is extremely advantageous. [Brief description of the drawings]

[0015] [Figure 1] 1 is a schematic diagram of a material transport path showing a first embodiment of the present invention; [Diagram 2] Flowchart showing the material conveying and dispensing process DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The geopolymer composition of this embodiment is used for structures in, for example, civil engineering, architecture, etc., and is composed of raw materials containing an active filler and an alkaline raw material.

[0017] The active filler is a powder that is activated and solidified by mixing with an alkaline raw material, and is made of an alkali-active amorphous powder such as fly ash (coal ash), metakaolin, silica fume, or blast furnace slag.

[0018] As the alkali source, sodium metasilicate powder is used, and it is also possible to use a mixture of sodium metasilicate and water glass.

[0019] The active filler and the alkali raw material are mixed with water, and the geopolymer in a slurry state is poured into the water, whereby construction is carried out underwater. At that time, aggregate and fiber may be mixed.

[0020] In order to improve the workability of geopolymers underwater, high material non-separation properties are required, so that the material does not easily separate in water in still or flowing water environments. To achieve this, it is effective to reduce the moisture content of the raw material, but since water glass, which is generally used as the alkaline raw material for geopolymer compositions, contains at least 45% water, there is a limit to how much water can be reduced when water glass is used as the main alkaline raw material. In this embodiment, by using sodium metasilicate powder as an alkaline raw material, the moisture content of the raw material is significantly lowered compared to when water glass is mainly used, and a geopolymer composition that has the underwater non-separation properties and strength that allows construction even underwater has been realized.

[0021] In this case, by making the molar ratio of the sodium contained in the sodium metasilicate powder to the sum of all sodium and potassium in the alkaline raw material 0.4 or more (preferably 0.5 or more), and the molar ratio of the sum of the sodium and potassium contained in the hydroxide to the sum of all sodium and potassium in the alkaline raw material 0 or more and less than 0.3 (preferably 0 or more and 0.16 or less), the density of the geopolymer composition is increased, making it easy to work with and ensuring sufficient strength.

[0022] Generally, geopolymers require a heating and curing process at, for example, 60°C to develop sufficient strength, but to obtain sufficient strength through underwater solidification, they need to be able to develop the necessary strength even in a temperature environment of around 20°C to 40°C.

[0023] In this embodiment, by setting the moisture content of the raw material to less than 30%, even if the filling work is performed underwater where heat curing cannot be performed, it is possible to obtain high strength almost equivalent to that obtained by heat curing in air. As a result, even without the use of additives such as organic thickeners and surfactants as in conventional cement-based materials, the viscosity and material separation resistance in water are high, making it possible to carry out underwater construction of structures that require high strength.

[0024] In addition, in large-scale construction where the area cannot be filled in a single application, the concrete is filled intermittently, a process known as overlay application. However, if the hardening speed is too fast, the adhesive strength at the interface between the overlays decreases, so in the past it was necessary to use admixtures.

[0025] In this embodiment, the bonding strength at the interface between the overlapping layers can be increased by making the molar ratio of the total of all sodium and potassium in the alkali raw material less than 0.3. Since NaOH is easily dissolved in the surrounding water, if the molar ratio is 0.3 or more, the geopolymer component at the interface between the overlapping layers becomes diluted, which reduces the bonding strength at the interface between the overlapping layers.

[0026] On the other hand, when a geopolymer composition is filled into water, the interface with the surrounding water becomes a soft unhealthy layer (unhardened layer). The faster the geopolymer solidification reaction rate, the thinner this unhealthy layer becomes. Therefore, by setting the combined molar ratio of sodium and potassium contained in the hydroxide (Na / (Na+K)) to 0.5 or more, it is possible to increase the solidification reaction rate of the geopolymer composition and reduce the thickness of the unhealthy layer.

[0027] Thus, according to this embodiment, sodium metasilicate powder is used as the alkali raw material of the geopolymer composition that is filled in water and solidified, so the water content of the raw material can be significantly reduced compared to when water glass is mainly used as the alkali raw material, and the geopolymer can be made dense and the underwater filling strength can be increased. As a result, even without using additives such as organic thickeners and surfactants as in conventional cement-based materials, the viscosity and material non-separation in water are high, and it is possible to express high strength similar to that in air even in water where warm curing cannot be performed, so that it is possible to apply it to underwater structures that take advantage of the characteristics of geopolymers such as high chemical resistance and element containment.

[0028] 1 and 2 are embodiments showing a method for producing the geopolymer composition.

[0029] In this embodiment, a first material conveying path 1 for conveying a first material A (mainly a powder) containing at least an active filler and a second material conveying path 2 for conveying a second material B (mainly a liquid) containing at least water or an alkaline solution are used, and the first material A conveyed from the first material conveying path 1 is mixed with the second material B conveyed from the second material conveying path 2 to produce a geopolymer composition. In addition, a discharge nozzle 10 is used to mix and discharge the first material A and the second material B.

[0030] The first material conveying path 1 consists of a powder flow passage (e.g., a hose, tube, etc.) connected to the discharge nozzle 10, and the first material A supplied to the powder pump 3 from a silo or the like (not shown) is pressurized to the discharge nozzle 10 by compressed air supplied to the powder pump 3 from an air compressor 4.

[0031] The second material transport path 2 is made up of a fluid flow passage (for example, a hose, a tube, etc.) connected to the discharge nozzle 10, and the second material B is pressure-fed to the discharge nozzle 10 by the pump 5.

[0032] When the geopolymer composition of this embodiment is applied at an underwater construction site, as shown in FIG. 2, first, the stirred first material A is charged from the silo to the powder compressor 3 of the first material conveying path 1 (S1). Next, the first material A is pressure-fed from the powder compressor 3 to the discharge nozzle 10 via the first material conveying path 1 by compressed air from the air compressor 4 (S2), and the second material B is pressure-fed to the discharge nozzle 10 via the second material conveying path 2 by the pump 5 (S3). As a result, the mixture C of the first and second materials A and B mixed in the discharge nozzle 10 is discharged from the discharge nozzle 10 to the construction site (S4). In the discharged mixture C, the first material A reacts with the second material B and hardens, producing geopolymer concrete.

[0033] When applying geopolymer concrete by spraying, a mixture C of the first and second materials A and B is discharged from the discharge nozzle 10 onto the water surface and poured into a construction site, such as a formwork installed underwater. Since the geopolymer concrete of the present invention has high viscosity and high material separation resistance in water, it is poured into the construction site without dispersing in the water.

[0034] In this case, it is preferable that the molar ratio of the total of all sodium and potassium in the alkali raw material is less than 0.7 (for example, 0.5). As described above, when the molar ratio is less than 0.3, the bonding strength at the overlapping boundary surface of intermittent application can be increased, but in the case of continuous application into water by spray application, it is advantageous to increase the molar ratio to increase the hardening speed in order to prevent the dispersion of the material during descent into water, but if the molar ratio is too high, the strength decreases, so it is preferable that the molar ratio is less than 0.7.

[0035] In this way, a first material conveying path 1 for conveying at least a first material A containing an active filler and a second material conveying path 2 for conveying a second material B containing at least water are used, and a geopolymer composition is generated by adding a second material B conveyed from the second material conveying path 2 to the first material A conveyed from the first material conveying path 1, so that a powder material (first material A) and a liquid material (second material B) can be conveyed separately. As a result, compared to the case where the materials of the geopolymer composition are mixed and conveyed from the beginning, a high pressure conveying load due to viscosity is not generated, and it is possible to realize on-site construction of geopolymer concrete by long-distance pressure conveying.

[0036] Therefore, it is extremely advantageous for sites where materials must be transported long distances to the work site, such as underwater work in the ocean, rivers, etc. Also, in order to safely carry out work in an underwater environment in decommissioning work at a nuclear power plant, it is effective to discharge materials to the work site by remote control, and the present invention, which enables long-distance pressure transport, is extremely advantageous in such cases as well.

[0037] In this case, the first material A is transported along the first material transport path 1 by compressed air, and the second material B is pressurized by a pump 5 along the second material transport path 2, so that the same transport equipment as in the dry spraying method can be used, which is extremely advantageous in terms of practical application.

[0038] Furthermore, since a discharge nozzle 10 is used to mix and discharge the first material A discharged from the first material conveying path 1 with the second material B discharged from the second material conveying path 2, the material C mixed just before can be discharged from a single discharge nozzle 10, making it easy to carry out construction on site.

[0039] In addition, in the above embodiment, powdered raw materials such as active filler and alkali powder are used as the first material A, but a geopolymer raw material composition obtained by granulating some or all of the powdered raw materials into granules may also be used.

[0040] As a method for granulating the geopolymer raw material composition into granules, the so-called spray-dry granulation method can be used, in which the powder raw material is mixed with at least one of water, an alkaline solution, and a binder, the resulting slurry is sprayed into hot air, and then instantly dried to granulate. The binder is a substance that gives the powder raw material appropriate cohesiveness during the granulation operation, and is used as a binding medium between solid particles, taking into consideration strength (disintegrability), solubility, reactivity, etc. according to the application and purpose.

[0041] In addition, examples of granulation methods that can be used other than spray drying include an extrusion granulation method in which a slurry is extruded through a plurality of openings and cut into granules to form granules; a rolling granulation method in which a powdered raw material is rolled in a rotating drum or a rolling pan while a binder or water is sprayed onto it to form granules; an agitation granulation method in which a powdered raw material is granulated by adding a binder or water while being agitated with a rotating blade; and a fluidized bed granulation method in which the powder is fluidized and a binder or water is sprayed onto it to bond the particles.

[0042] In this way, by using a geopolymer raw material composition in which some or all of the powder raw materials are granulated as the first material A, the raw material can be easily measured, so that changes in the raw material mixing ratio can be suppressed and the performance stability of the geopolymer composition can be improved. In this case, since there is no need to measure multiple types of raw materials individually, the measuring process can be made more efficient and the risk of performance degradation due to measuring errors can be reduced.

[0043] In addition, since the transportability of the raw material can be improved, for example, in dry spraying construction, it becomes possible to pump large amounts of the first material A through the first material transport path 1, thereby improving productivity in underwater construction.

[0044] Furthermore, since the viscosity of the slurry can be reduced, the strength and durability of the geopolymer composition can be increased (improved acid resistance and salt damage resistance), and the viscosity can be reduced without the use of additives such as water reducers.

[0045] In addition, by increasing the particle size through granulation, the specific surface area is reduced, thereby reducing the effects of humidity on the premix material. Furthermore, by integrating multiple powders with different densities through granulation, the raw materials in the premix material can be made uniform.

[0046] Furthermore, if the particle size of the geopolymer raw material composition is too small, the effect of increasing the particle size will be reduced, so the average particle size of the granulated geopolymer raw material composition is preferably 10 μm or more. EXAMPLES

[0047] EXAMPLES Hereinafter, examples of the present invention will be described, but the present invention is not limited to these examples.

[0048] [Materials used] The geopolymer compositions of Examples 1 to 4, Reference Example 1, and Comparative Example 1 use metakaolin, silica fume, and fly ash as binders (active fillers), and sodium metasilicate powder and water glass as alkaline raw materials.

[0049] The geopolymer compositions of Examples 5 to 7, Reference Example 2, and Comparative Example 2 use metakaolin and silica fume as binders (active fillers), and sodium metasilicate powder and water glass as alkaline raw materials.

[0050] [Mole ratio of raw materials] In Examples 1 to 4, Reference Example 1 and Comparative Example 1, the molar ratio of silicon to aluminum (Si / Al) was 2.2, and the molar ratio of the sum of sodium and potassium to aluminum ((Na+K) / Al) was 0.8.

[0051] The molar ratio of sodium in the sodium metasilicate powder to the total of all sodium and potassium in the alkali raw materials was 0.5 in Examples 1 to 3 and Reference Example 1, 0.65 in Example 4, and 0.35 in Comparative Example 1.

[0052] The molar ratio of the total of sodium and potassium contained in the hydroxide to the total of all sodium and potassium in the alkaline raw material was 0 in Examples 1 to 4 and Reference Example 1, and 0.3 in Comparative Example 1.

[0053] The total molar ratio of sodium and potassium in the hydroxide (Na / (Na+K)) was 0.5 in Examples 1 to 3 and Reference Example 1, and 0.65 in Example 4 and Comparative Example 1.

[0054] In Examples 5 to 7, Reference Example 2 and Comparative Example 2, the molar ratio of silicon to aluminum (Si / Al) was 2.2, and the molar ratio of the sum of sodium and potassium to aluminum ((Na+K) / Al) was 1.

[0055] The molar ratio of sodium contained in the sodium metasilicate powder to the total of all sodium and potassium in the alkaline raw material was 0.5 in Examples 5 and 6 and Reference Example 2, 0.65 in Example 7, and 0.35 in Comparative Example 2.

[0056] The molar ratio of the total of sodium and potassium contained in the hydroxide to the total of all sodium and potassium in the alkaline raw material was 0 in Examples 5 to 7 and Reference Example 2, and 0.3 in Comparative Example 2.

[0057] The total molar ratio of sodium and potassium in the hydroxide (Na / (Na+K)) was 0.5 in Examples 5 and 6 and Reference Example 2, and 0.65 in Example 7 and Comparative Example 2.

[0058] [Raw material moisture content] The moisture contents of the raw materials in Examples 1 to 4, Reference Example 1 and Comparative Example 1 were 25.2 for Example 1, Reference Example 1 and Comparative Example 1, 22.8 for Example 2, 19.7 for Example 3 and 25.7 for Example 4.

[0059] The moisture content of the raw materials in Examples 5 to 7, Reference Example 2 and Comparative Example 2 was 27.7 in Example 5, Reference Example 2 and Comparative Example 2, 25.3 in Example 6 and 28.5 in Example 7.

[0060] [Compressive strength test] Compressive strength tests of Examples 1 to 7 and Comparative Examples 1 and 2 were carried out according to the following procedures (1) to (6). (1) Fine aggregate is added to the geopolymer slurry and mixed to produce geopolymer mortar. (2) After pouring water at 20°C ± 3°C or 40°C ± 5°C up to a position 100 mm from the top of the mold, fill one mold with geopolymer mortar within 2 minutes. At this time, the filling is done by pouring the mortar into the water from the air above the water surface. (3) After filling the mold with mortar, leave it in the air for 15 minutes. (4) The mold is sealed and sealed and cured at a temperature equal to the water temperature during filling. (5) Polish the ends before strength testing. (6) Conduct uniaxial compressive strength tests when the material is aged 13 to 15 days.

[0061] In addition, in Reference Examples 1 and 2, filling in water was not performed, and after step (1), heating and curing at 60° C. was performed in air.

[0062] [Underwater non-separation test] An underwater non-separation test was carried out for Examples 1 to 7 and Comparative Examples 1 and 2 according to the following procedures (1) to (4). (1) Fine aggregate is added to the geopolymer slurry and mixed to produce geopolymer mortar. (2) Pour water at 20°C ± 3°C or 40°C ± 5°C into a transparent mold up to a position 100 mm from the top of the mold, then fill one mold with geopolymer mortar within 2 minutes. The filling is done by pouring the mortar into the water from the air above the water surface. (3) 10 seconds after the start of filling, visually observe the state of contamination inside the mold (turbidity caused by material that has separated from the filled material). The test result in which the water above the mortar is the most contaminated is regarded as 100%, and the other test results are evaluated in proportion to this. (4) Insert a steel ruler into the unsound layer of mortar and measure the thickness of the unsound layer.

[0063] [Overlap interface adhesion test] An overlapping interface adhesion test was carried out for Examples 1 to 7 and Comparative Examples 1 and 2 according to the following steps (1) to (3). (1) Fine aggregate is added to the geopolymer slurry and mixed to produce geopolymer mortar. (2) Pour water at 20°C ± 3°C or 40°C ± 5°C into a transparent mold up to a position 100 mm from the top of the mold, then fill one mold with geopolymer mortar within 2 minutes. The filling is done by pouring the mortar into the water from the air above the water surface. (3) Check the appearance of the mortar 2 hours or 24 hours after the start of filling to see if there is a boundary line, and strike it with a hammer to see if it cracks at the overlapping points.

[0064] [Test result 1] The following shows the results of tests carried out on Examples 1 to 4, Reference Example 1, and Comparative Example 1. Table 1 shows the results of a compressive strength test, Table 2 shows the results of a material non-separation test in water, and Table 3 shows the results of an overlapping interface adhesion test.

[0065] [Table 1]

[0066] [Table 2]

[0067] [Table 3]

[0068] According to the results of the compressive strength test, in comparison with Reference Example 1, which was subjected to heat curing at 60°C in air, Examples 1 to 4 had sufficient strength in a temperature environment of 40°C. In particular, as shown in Examples 1 to 3, the lower the moisture content of the raw material, the higher the strength. Moreover, Example 4, in which the molar ratio of the sodium contained in the sodium metasilicate powder to the sum of all sodium and potassium in the alkaline raw material was high, had a higher strength than Example 1, in which the molar ratio was low. Comparative Example 1, in which the molar ratio of the total of sodium and potassium contained in the hydroxide to the total of all sodium and potassium in the alkaline raw material was 0.3, showed that the strength was hardly increased even when the curing temperature was increased.

[0069] According to the results of the underwater non-segregation test, the water above the mortar with a high raw material moisture content was the most polluted in Example 1, whereas the lower the raw material moisture content, the less the pollution, as shown in Examples 2 and 3. Moreover, Example 4, in which the molar ratio of the sodium contained in the sodium metasilicate powder to the total of all sodium and potassium in the alkaline raw material is high, showed less pollution even though the raw material moisture content was higher than in Examples 2 and 3. Moreover, the results showed that the thickness of the unhealthy layer was thinner in Example 4, in which the molar ratio (Na / (Na+K)) of the total of sodium and potassium contained in the hydroxide was high.

[0070] According to the results of the overlapping boundary adhesion test, a boundary line was confirmed in all cases, both 2 hours and 24 hours after the start of filling, except for Example 3. In Example 3, a boundary line was confirmed 24 hours after the start of filling, but not confirmed 2 hours after the start of filling. In addition, as a result of impact with a hammer, all cracked at the boundary line 24 hours after the start of filling, but only Comparative Example 1 cracked at the boundary line 2 hours after the start of filling. Cracks were confirmed in Example 3.

[0071] [Test result 2] The following shows the results of tests carried out on Examples 5 to 7, Reference Example 2, and Comparative Example 2. Table 4 shows the results of the compressive strength test, Table 5 shows the results of the material non-separation test in water, and Table 6 shows the results of the overlapping interface adhesion test.

[0072] [Table 4]

[0073] [Table 5]

[0074] [Table 6]

[0075] According to the results of the compressive strength test, in comparison with Reference Example 2, which was subjected to heat curing at 60°C in air, Examples 5 to 7 had sufficient strength in a temperature environment of 40°C. In particular, as shown in Example 5, the lower the moisture content of the raw material, the higher the strength. Furthermore, in Comparative Example 2, in which the molar ratio of the total of sodium and potassium contained in the hydroxide to the total of all sodium and potassium in the alkaline raw material was 0.3, the results showed that the strength hardly increased even when the curing temperature was increased.

[0076] According to the results of the underwater non-segregation test, the water above the mortar with a high raw material moisture content was the most polluted in Example 5, whereas the lower the raw material moisture content, the less the pollution, as shown in Example 6. Also, in Example 7, in which the molar ratio of the sodium in the sodium metasilicate powder to the total of all sodium and potassium in the alkaline raw material was high, the result was that the pollution was almost the same even though the raw material moisture content was higher than that of Example 6. Also, the result was that the thickness of the unhealthy layer was thinner in Example 7, in which the molar ratio (Na / (Na+K)) of the total of sodium and potassium in the hydroxide was high.

[0077] According to the results of the overlapping boundary adhesion test, a boundary line was confirmed in all cases both 2 hours and 24 hours after the start of filling. In addition, as a result of impact with a hammer, all cracks occurred at the boundary line 24 hours after the start of filling, but only Comparative Example 2 cracked at the boundary line 2 hours after the start of filling.

[0078] From the above test results 1 and 2, it was confirmed that the lower the moisture content of the raw material, the higher the strength and the better the anti-separation properties in water. It was also confirmed that the lower the molar ratio of the total of sodium and potassium in the hydroxide to the total of all sodium and potassium in the alkaline raw material, the better the adhesion of the overlapping interface. Furthermore, it was confirmed that the higher the molar ratio of the total of sodium and potassium in the hydroxide (Na / (Na+K)), the faster the geopolymer solidification reaction rate and the smaller the thickness of the unhealthy layer can be.

[0079] Furthermore, according to the test results 1 and 2, when Examples 1 to 4, which used three types of active fillers, i.e., metakaolin, silica fume and fly ash, were compared with Examples 5 to 7, which used two types of active fillers, i.e., metakaolin and silica fume, the results showed that Examples 1 to 4 were superior to Examples 5 to 7 in terms of underwater non-separation, and Examples 5 to 7 were superior to Examples 1 to 4 in terms of overlapping interface adhesion. [Explanation of symbols]

[0080] 1...first material transport path, 2...second material transport path, A...first material, B...second material.

Claims

1. A geopolymer composition comprising a mixture of an active filler, an alkaline raw material, and water, and filled in water to solidify; Sodium metasilicate powder was used as the alkali source. A geopolymer composition comprising:

2. The molar ratio of sodium contained in the sodium metasilicate powder to the total amount of sodium and potassium contained in the alkali raw material is 0.4 or more. The geopolymer composition of claim 1.

3. The molar ratio of the total of sodium and potassium contained in the hydroxide to the total of all sodium and potassium contained in the alkali raw material is less than 0.

3. The geopolymer composition of claim 1.

4. The molar ratio of sodium to the sum of sodium and potassium (Na / (Na+K)) is 0.5 or more. The geopolymer composition of claim 1.

5. The moisture content of the raw material is less than 30%. The geopolymer composition of claim 1.

6. As the material, a geopolymer raw material composition obtained by granulating part or all of the powder material is used. The geopolymer composition of claim 1.

7. A method for producing a geopolymer composition comprising mixing an active filler, an alkaline raw material, and a material containing water, and filling the mixture in water and solidifying the mixture. The alkali raw material is sodium metasilicate powder, A first material conveying path conveying a first material including at least an active filler and a second material conveying path conveying a second material including at least water or an alkaline solution are used; A geopolymer composition is produced by adding a second material conveyed from a second material conveying path to a first material conveyed from a first material conveying path, and the resulting composition is filled in water. A method for producing a geopolymer composition.

8. The molar ratio of the total of sodium and potassium contained in the hydroxide to the total of all sodium and potassium contained in the alkali raw material is less than 0.

7. The method for producing the geopolymer composition according to claim 7.

9. As the material to be transported by the first material transport path, a geopolymer raw material composition obtained by granulating part or all of the powder material is used. The method for producing the geopolymer composition according to claim 7.

Citation Information

Patent Citations

  • JP1975091519A